2023
DOI: 10.9734/ajfar/2023/v25i4678
|View full text |Cite
|
Sign up to set email alerts
|

Fish Sanctuaries as an Ecological Approach to Management for Restoring Fish Biodiversity: A Study on Chikadubi Beel Fish Sanctuary, Bangladesh

Md. Shahin Alam,
Saokat Ahamed,
Parvez Chowdhury
et al.

Abstract: The fish biodiversity of open water is reducing as rice culture has been intensified due to other environmental threats. The establishment of a fish sanctuary is a way to conserve fish for future generation. A study was conducted to know the impact of the sanctuary on fish biodiversity for six months from August to December 2020. Various Participatory rural appraisal (PRA) tools were used such as Questionnaire interviews, focus group discussion (FGD), Catch monitoring and cross-check interviews were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…DoF [15] estimates that there are roughly 115 freshwater fish species in the Bhairab River, divided into 13 orders and 31 families. Alam et al, [10] reported that 78 fish species were recorded in the Chikadubi beel fish sanctuary of Dingaputa haor. Hossain et al [16] recorded a total of 115 fish species in 29 Families and 4 shellfish species in 2 families (3 prawns and a crab).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DoF [15] estimates that there are roughly 115 freshwater fish species in the Bhairab River, divided into 13 orders and 31 families. Alam et al, [10] reported that 78 fish species were recorded in the Chikadubi beel fish sanctuary of Dingaputa haor. Hossain et al [16] recorded a total of 115 fish species in 29 Families and 4 shellfish species in 2 families (3 prawns and a crab).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of awareness of human is causing huge damage to water resources across the nation. As a result of these factors, plant and wildlife diversity has been declining over the planet [10]. International Union for conservation of nature (IUCN) assessed total number of available freshwater fish species in Bangladesh was 260 of which, 64 species have been found Threatened, which is 25.3% of the total species [11].…”
Section: Introductionmentioning
confidence: 99%